Rhetorical Moves and Linguistic Features of Research Article Abstracts by Indonesian Authors in Applied Linguistics Published in National Journal - Astria, Hellen; Arsyad, Safnil; Diani, Irma (English Education Study Program Faculty of Teacher Training and Education, 2023)
Abstract is a very important part of a research article. It is the first section to be read by readers and if readers are not impressed in reading this section, they will unlikely continue reading the article. This study aims to find the rhetorical moves, rhetorical patterns, and linguistics features; tenses, voice forms, and that-complement clause of RA abstracts by Indonesian authors in Applied Linguistics published in National Journal. This study used mix-methods by analyzing the move structure, rhetorical patterns, and the linguistic feature of the twenty four RA abstracts extracted from Edu-ling: Journal of English Education and Linguistics as the sample of this study. The results show that: 1) The dominant moves used are Move 2 (Purpose), Move 3 (Methodology), and Move 4 (Results); 2) The dominant rhetorical patterns used are the four model patterns; 3) The linguistic features shows the dominant tense is Simple Past Tense; the dominant voice forms is active forms, and the uses of that-complement clause in Move 4. This study concludes that there is an unwareness of the authors about the latest common inventions about the rhetorical moves. Further research is suggested to be concerned on that-complement clause.